2019
DOI: 10.1021/acs.jafc.9b03961
|View full text |Cite
|
Sign up to set email alerts
|

Residue Analysis and Risk Assessment of Oxathiapiprolin and Its Metabolites in Cucumbers under Field Conditions

Abstract: In this study, a rapid, sensitive, and selective method was established for the detection of oxathiapiprolin and the metabolite IN-E8S72, as well as its glucose conjugate IN-SXS67 in cucumber using modified QuEChERS procedure combined with HPLC−MS/MS. The LOQs for all compounds were 0.02 mg kg −1 , and the average recoveries were 77.4−111.3% with RSDs of 1.0−8.5%. Under the optimized conditions, the established method was successfully used to determine field samples in dissipation and terminal residue studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Feng et al analyzed the uptake and distribution of oxathiapiprolin, IN-WR791 and IN-E8S72 residues in tomatoes, cucumbers, lettuce, and Chinese cabbage to test the viability of applying the dynamic plant uptake model (dynamiCROP) in modeling pesticide residues in other crops [21,22]. Wang et al established a modified QuECh-ERS purification scheme, and used LC-MS/MS detection for oxathiapiprolin, IN-SXS67 and IN-E8S72 residues in cucumbers; recovery rates ranged from 77.4 to 111.3%, RSDs were 1.0−8.5%, and LOQs were 0.02 mg/kg, and the dissipation half-lives for oxathiapiprolin in cucumbers ranged from 2.4 to 4.0 days [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feng et al analyzed the uptake and distribution of oxathiapiprolin, IN-WR791 and IN-E8S72 residues in tomatoes, cucumbers, lettuce, and Chinese cabbage to test the viability of applying the dynamic plant uptake model (dynamiCROP) in modeling pesticide residues in other crops [21,22]. Wang et al established a modified QuECh-ERS purification scheme, and used LC-MS/MS detection for oxathiapiprolin, IN-SXS67 and IN-E8S72 residues in cucumbers; recovery rates ranged from 77.4 to 111.3%, RSDs were 1.0−8.5%, and LOQs were 0.02 mg/kg, and the dissipation half-lives for oxathiapiprolin in cucumbers ranged from 2.4 to 4.0 days [23].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al. established a modified QuEChERS purification scheme, and used LC–MS/MS detection for oxathiapiprolin, IN‐SXS67 and IN‐E8S72 residues in cucumbers; recovery rates ranged from 77.4 to 111.3%, RSDs were 1.0−8.5%, and LOQs were 0.02 mg/kg, and the dissipation half‐lives for oxathiapiprolin in cucumbers ranged from 2.4 to 4.0 days [23].…”
Section: Introductionmentioning
confidence: 99%
“…Oxathiapiprolin has one chiral carbon atom and thus consists of a pair of enantiomers. To date, only a few of studies have focused on monitoring of racemic oxathiapiprolin, with several residue analytical methods for oxathiapiprolin in fruits and vegetables and environmental samples such as soil, water, and sediments [3, 1113]. However, to date, data about oxathiapiprolin in food and environmental samples at enantiomeric level are unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…The MEs (suppression and enhancement of signals) were examined to avoid false-negative or false-positive results. The ME was evaluated using the following equation [39].…”
Section: Quantification and Methods Performancementioning
confidence: 99%
“…According to past studies, mixing organic acids (including formic acid [39], phosphate [41], Na 2 EDTA-Mcllvaine [38,42]) with methanol [37] or ACN [43] is the most effective extraction solution with good recovery efficiency and has good reproducibility when analyzing multiple antibiotic residues in environmental matrices. Ferhi et al [34] demonstrated that ACN and citric acid-phosphate buffer can be used to efficiently extract eight antibiotics from the soil.…”
Section: Choice Of Extractantmentioning
confidence: 99%